Developing the professional skills of social work students in the school setting from the perspective of professors A field study - غفور, ا.م.د. رزگار مصطفى غفور (Sulaimani Journal for Humanities, 2026)
This study aims at identifying the development of professional preparation for students of the Social Work Department in the school field from their teacher's point of view. Developing professional preparation is an intentional process that aims at raising the level of professional practice for students of the Department of Social Work in the future. The school field is considered one of the most important areas of social work; therefore, activating the professional preparation for the students contributes to achieving the development of their preparations abilities and skills that are necessary to refine and improve their knowledge. In this study, we focus on developing the professional preparation of the Social Work Department students in the school field, by that we mean preparing students theoretically and practically in order to acquire knowledge and experience, as well as Professional skills, and modern positive trends in developing their abilities in order to work as social workers in schools in the future. Preparing students of the Social Work Department is a necessary requirement to develop their preparation theoretically and practically, considering that the professional preparation of students is one of the basic pillars and an effective element in the progress of their preparation by providing them with knowledge and information related to the professional practice in the field of social work and to develop the professional skills that students need to work actively in schools. This study is considered a qualitative one as it has adopted a descriptive analytical approach, in which the study sample included (12) professors who constitute 66.66% of the teaching staff in the Department of Social Work at the College of Humanities in Sulaymani University. The study also employed interview technique as a tool for collecting data, through which the study reached a number of conclusions, the most important one is the fact that the professional preparation of the students of the Social Work Department to work in schools has contributed to achieving the goals of developing the students’ professional progress, but it is not at the required level. Finally, and in light of the results, the researcher has developed a set of recommendations and suggestions.